2023
DOI: 10.3390/polym15040869
|View full text |Cite
|
Sign up to set email alerts
|

Device Modeling of Efficient PBDB-T:PZT-Based All-Polymer Solar Cell: Role of Band Alignment

Abstract: In this study, we present some design suggestions for all-polymer solar cells by utilizing device simulation. The polymer solar cell under investigation is formed by a photoactive film of a blend comprising PBDB-T as a polymer donor and PZT as a polymerized small molecule acceptor. The initial cell is based on a fabricated cell whose structure is ITO/PEDOT:PSS/PBDB-T:PZT/PFN-Br/Ag, which has a power conversion efficiency (PCE) of about 14.9%. A calibration procedure is then performed by comparing the simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The alignment of the energy band is essential in thin film solar cells. However, there are several instances when it is clear that the theoretical predictions and the band alignment as determined by experiment differ significantly [76, 77]. The device's properties may significantly differ as a result of this variance.…”
Section: Resultsmentioning
confidence: 99%
“…The alignment of the energy band is essential in thin film solar cells. However, there are several instances when it is clear that the theoretical predictions and the band alignment as determined by experiment differ significantly [76, 77]. The device's properties may significantly differ as a result of this variance.…”
Section: Resultsmentioning
confidence: 99%
“…All-polymer solar cells (APSCs), which utilize a physical blend of pand n-type polymers as the photoactive layer, are a subtype of organic PVs gaining traction for IPV applications, offering superior mechanical stability and morphological durability [9]. Although APSCs have been extensively researched in outdoor applications [10][11][12][13][14][15], their applications in indoor photovoltaic applications still lag. Although a few studies have demonstrated high V OC and PCE in APSCs tailored for IPV applications, these investigations show the potential of APSCs as efficient and durable IPV solutions [16].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, simulation studies are particularly necessary to provide a more effective and economical approach to optimizing the tandem and recognizing the physical phenomena of cell performance. Different blends have been investigated, and optimization steps have been performed to boost the PCE of the proposed solar cells [39][40][41][42][43]. In addition, many research simulation studies related to CIGS can also be found concerning the impact of defect states, bandgap grading, ultra-thin film absorber, and many other effects, whether for a single-junction CIGS or when incorporating CIGS as a bottom subcell in a TSC [44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%